Trade and economic growth in developing countries: Evidence from sub-Saharan Africa - Pam Zahonogo (Journal of African Trade, 2016)
This study investigates how trade openness affects economic growth in developing countries, with a focus on sub-Saharan Africa (SSA). We use a dynamic growth model with data from 42 SSA countries covering 1980 to 2012. We employ the Pooled Mean Group estimation technique, which is appropriate for drawing conclusions from dynamic heterogeneous panels by considering long-run equilibrium relations. The empirical evidence indicates that a trade threshold exists below which greater trade openness has beneficial effects on economic growth and above which the trade effect on growth declines. The evidence also indicates an inverted U-curve (Laffer Curve of Trade) response, robust to changes in trade openness measures and to alternative model specifications, suggesting the non-fragility of the linkage between economic growth and trade openness for sub-Saharan countries. Our findings are promising and support the view that the relation between trade openness and economic growth is not linear for SSA. Accordingly, SSA countries must have more effective trade openness, particularly by productively controlling import levels, in order to boost their economic growth through international trade.
Keywords: F14; O40; 330; Trade openness; Economic growth; Sub-Saharan Africa